Exploring ESG practices for family businesses: A bibliometric analysis - GMATI, Hinda; CHABBOUH, Insaf (Edelweiss Applied Science and Technology, 2025)
The aim of this study is to map the development of research on Environmental, Social, and Governance (ESG) practices for family business. As significant role-players in the global economy, family-owned companies face multiple sustainability pressures from various stakeholders. Their attractiveness for ESG engagement may be due to their special governance and long disturbance orientation, but the literature does not provide a coherent result for the drivers. Adopting bibliometric analysis of publications indexed in the Web of Science, and using Bibliometrix R-package, this study visualizes the intellectual structure, influential works and emerging topics of the ESG-family businesses research landscape. It analyzes co-authorship, co-citation, and keyword co-occurrence networks, and identify research clusters and thematic trends. The findings offer a comprehensive overview of ESG practices for family firms’ research. It combines these insights to offer practical guidance for managerial decisions, highlighting how family firms can strategically leverage ESG practices for enhanced long-term value and stakeholder engagement. Moreover, it demonstrates that the development of ESG scholarship illuminates economic designs of management under which family businesses can steer the complex dynamics of regulation, competitiveness, and sustainability challenges.